Citizen Empowered Mapping - Leitner, Michael; Jokar Arsanjani, Jamal (Geotechnologies and the Environment, 2017)
This book promotes the exploitation of novel and emerging approaches for mapping environmental and urban informatics empowered by citizens. Chapters are grouped in three sections representing the main subjects. The first section describes data acquisition and modeling. The second section focuses on the quality and reliability of data. The final section presents different methods of environmental monitoring and perception. The book includes diverse case studies from Mexico, the United States and Czech Republic.Topics covered in Citizen Empowered Mapping are of interest for research scholars, practitioners, postgraduates, and professionals from a variety of disciplines including geography, environmental science, geographic information science, social science, and computer science.